POLI, Mémoires d’une femme pygmée - Bécache, Jean-Daniel (France, 2011)
Amandine, a young woman from Cameroon, finds a book about a Baka midwife named Poli at a local market. The more she learns about Poli’s life, the more curious she becomes about Pygmy culture. Amandine journeys into the jungle to meet the Pygmies and uncover the many challenges they face in the modern world.
Verzio Film Festival Submission
Duration: 01:01:00
Verzio Film Festival Submission
Keywords: Documentary films